Protein tyrosine phosphatase 1B inhibitors isolated from Artemisia roxburghiana. (3rd July 2016) - Shah, Muhammad Raza; Ishtiaq,; Hizbullah, Syed Muhammad; Habtemariam, Solomon; Zarrelli, Armando; Muhammad, Akhtar; Collina, Simona; Khan, Inamulllah
Abstract: Artemisia roxburghiana is used in traditional medicine for treating various diseases including diabetes. The present study was designed to evaluate the antidiabetic potential of active constituents by using protein tyrosine phosphatase 1B (PTP1B) as a validated target for management of diabetes. Various compounds were isolated as active principles from the crude methanolic extract of aerial parts of A. roxburghiana . All compounds were screened for PTP1B inhibitory activity. Molecular docking simulations were performed to investigate the mechanism behind PTP1B inhibition of the isolated compound and positive control, ursolic acid. Betulinic acid, betulin and taraxeryl acetate were the active PTP1B principles with IC50 values 3.49 ± 0.02, 4.17 ± 0.03 and 87.52 ± 0.03 µM, respectively. Molecular docking studies showed significant molecular interactions of the triterpene inhibitors with Gly220, Cys215, Gly218 and Asp48 inside the active site of PTP1B. The antidiabetic activity of A. roxburghiana could be attributed due to PTP1B inhibition by its triterpene constituents, betulin, betulinic acid and taraxeryl acetate. Computational insights of this study revealed that the C-3 and C-17 positions of the compounds needs extensive optimization for the development of new lead compounds.